Overload, Stress, and Satisfaction: Does It Impact Auditor's Intentions to Resign? - Ananta Wahyu Sasongko; Farhani Kautsar Nugraha; Putriana Sriwijianingsih (Master of Accounting Universitas Trunojoyo Madura, 2023)
The study aimed to investigate the impact of work overload, work-related stress, and job satisfaction on the turnover intentions of auditors in the